Analysis design for assembly by mtm-2 (methods time measurement-2) for wood joints in furniture - Sakkarin Choodoung (2018)
This research study assembly process of a study of Wood Joints with Motion Time Study MTM-2 (Methods Time Measurement-2) and DFA (Design for Assembly) an assessment of the ability to assembly in the Feeding and Fitting. with LUCAS Assembly Evaluation Method for the results of the assessment and find the good-bad points of the assessment was applied. Wood Joint Index for this analysis is the feeding and fitting should not exceed 2.5The pivot of the three groups in terms of feeding Index did not exceed 2.5The advantages of the assessments, when applied to the wood. In general, the nature of Wood Joints must rely on to tool help in almost all assemble of the joints. Each tool is the difficulty of performing it.And in the Entrance of the parts are in a bad score. Tolerance in the 0.2to 0.3mm at the Wood Joint this is limitation is that the scores of these problems. So both of these topics for Wood Joints may be more table to the assessment more accurate and led to the development process for next time. © (2012) Trans Tech Publications, Switzerland.